IS INDUSTRIAL SECTOR REALLY SUPERIOR IN CENTRAL JAVA? - Tamami, Tias Ismi (Advances in Social Sciences Research Journal, 2018)
This research aimed to analyze typology and potential sector in Regency/City of Central Java Surakarta. Data employed was secondary one deriving from BPS (Central Bureau of Statistics) and Financial Balance Directorate of Financial Ministry. The method employed was Klassen’s Typology analysis, Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ). The result of analysis using Klassen’s Typology showed that there were 5 Regencies/Cities belonging to 1st quadrant or high growth and high income, 5 to 2nd quadrant or high income but low growth, 15 to high growth but low income, and 9 to 4th quadrant or low growth and low income regions. Meanwhile, the result of SLQ and DLQ analysis showed that Processing Industry Sector is the only sector belonging to Superior Category. Agricultural, Forestry, and Fishery sector, Wholesale and Retail Trading, automobile and motorcycle repairing belonged to prospective categories. Based on this research, it can be conclude that government should give special attention to non-base sectors in order to be more optimal. The way that the road of insfrastructure so it can connect to District/Cities in Central Java for facilitating the distribution of goods needed by the community. Keywords: Klassen’s typology, Static Location Quotient, Dynamic Location Quotient, Economic Growth of Central Java